Mirabeau (gauche) résiste l'ordre du Roi, le 23 Juin. Haut-relief de la Chambre des députés - Dalou, Auguste,
Mirabeau (gauche) résiste l'ordre du Roi, le 23 Juin. Haut-relief de la Chambre des députés.